2015
DOI: 10.1103/physrevstper.11.020116
|View full text |Cite
|
Sign up to set email alerts
|

Identifying student difficulties with entropy, heat engines, and the Carnot cycle

Abstract: We report on several specific student difficulties regarding the Second Law of Thermodynamics in the context of heat engines within upper-division undergraduates thermal physics courses. Data come from ungraded written surveys, graded homework assignments, and videotaped classroom observations of tutorial activities. Written data show that students in these courses do not clearly articulate the connection between the Carnot cycle and the Second Law after lecture instruction. This result is consistent both with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 27 publications
1
31
0
3
Order By: Relevance
“…In 2015, Dreyfus [1] thoroughly catalogued and summarized prior research on student learning in thermodynamics and statistical mechanics across the disciplines of physics, chemistry, and biology. Current PER literature on upperdivision thermal physics is limited, and work specifically related to entropy has mostly explored its thermodynamic and macroscopic contexts such as ideal gases [2], heat engines [3], thermal equilibrium [4], and the 2 nd law [5,6]. Other research from across the natural sciences also has addressed students' understanding of entropy [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Dreyfus [1] thoroughly catalogued and summarized prior research on student learning in thermodynamics and statistical mechanics across the disciplines of physics, chemistry, and biology. Current PER literature on upperdivision thermal physics is limited, and work specifically related to entropy has mostly explored its thermodynamic and macroscopic contexts such as ideal gases [2], heat engines [3], thermal equilibrium [4], and the 2 nd law [5,6]. Other research from across the natural sciences also has addressed students' understanding of entropy [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies across these disciplines have found students have particular difficulties distinguishing between heat and temperature [12][13][14]. Other investigations have looked at student difficulties with entropy [15][16][17][18], appropriate applications of the ideal gas law [19,20], and energy in the context of the first law of thermodynamics [21,22]. Most of these studies have investigated student conceptual understanding in the realm of introductory thermodynamics content, mainly at the high school and introductory-college level [5].…”
Section: A Student Content Understandingmentioning
confidence: 99%
“…Some researchers have investigated student reasoning in thermal physics through interviews, reviews of student coursework, or conceptual assessments, while others have utilized tutorials. In particular, Smith et al created tutorials to investigate student reasoning using the Boltzmann factor to compare relative probabilities of states [23] and to address students' conceptions of entropy when approaching Carnot cycles [15]. We utilized a subset of questions from these tutorials to inform item development for our assessment.…”
Section: A Student Content Understandingmentioning
confidence: 99%
“…Members of the University of Maine Physics Education Research Laboratory and former members of the group who are now collaborating faculty from Rowan University and North Dakota State University contributed two articles on empirical research of student thinking as well as on the development of curricular materials for upper level thermodynamics statistical mechanics. One article, by Smith et al [36] presents evidence from written work and interviews of persistent student difficulties with heat engines and the second law. The second article by Smith, Mountcastle, and Thompson [37] focuses on student understanding of the Boltzmann factor and its connections to multiplicity and entropy.…”
Section: B Thermodynamics and Statistical Mechanicsmentioning
confidence: 99%